Administrative Stressors and Islamic Coping Strategies Among Muslim Primary Principals in Malaysia: A Mixed Method Study - Tahir L.M.; Khan A.; Musah M.B.; Ahmad R.; Daud K.; Al-Hudawi S.H.V.; Musta'Amal A.H.; Talib R. (Springer New York LLC, 2024)
Indexed by WOS/SCOPUS/ERA